Pengaruh Penggunaan Android dan E-Learning terhadap Hasil Belajar pada Mata Pelajaran IPS Siswa Kelas VII-A MTs Al Mujahidi Tembokrejo Gumukmas Jember - Utami, Sri; Kustiyowati, Kustiyowati; Muis, Abdul (ISLAMIKA, 2024)
The aim of this research is to assess the impact of Android and E-learning usage on the academic outcomes of IPS subjects among seventh-grade students in MTs Al Mujahidi Tembokrejo Gumukmas Jember during the academic year 2022-2023. This study employs a correlational approach, with the independent variables involving the use of Android and E-learning, while the dependent variable is student academic achievement. Data collection methods include questionnaires, documentation, and interviews, followed by analysis using descriptive analysis and multiple linear regression with the assistance of SPSS v. 23 for Windows. The results indicate a positive correlation between the use of Android and academic achievement, as well as between the use of E-learning and academic achievement. Furthermore, the analysis reveals that the combined use of Android and E-learning significantly influences student academic outcomes. Consequently, it can be concluded that the utilization of Android and E-learning contributes positively to enhancing the academic performance of seventh-grade students at MTs Al Mujahidi Tembokrejo Gumukmas Jember during the academic year 2022-2023. This research provides further insights into the integration of technology in education and its potential to improve student learning outcomes.